Prone vs Supine Positioning for Femoral Derotation Osteotomy: Kinematic and Physical Examination Outcomes Suggest Both Can Achieve Desired Results. Issue 1 (February 2022) - Givon, Uri; Drefus, Lisa; Murray-Weir, Mary; Lenhoff, Mark; Burket-Koltsov, Jayme C.; Dodwell, Emily R.; Scher, David M.
Background : Femoral derotation osteotomy (FDO) for correction of internal rotation gait resulting from cerebral palsy (CP) can be performed with the patient in the prone or supine position. It is not known whether patient positioning during FDO affects the change in hip rotation. Purpose/Questions : We sought to compare the change in hip rotation following FDO performed on patients with CP in the prone or supine position through kinematic analysis. Methods : We conducted a consecutive retrospective cohort study of children with CP, ages 3 to 18 years and with Gross Motor Function Classification System (GMFCS) levels I to III, who underwent prone or supine FDO and pre- and postoperative motion analysis. The prone group included 37 patients (68 limbs) between 1990 and 1995. The supine group included 26 patients (47 limbs) between 2005 and 2015. The groups were matched for gender, age, and GMFCS level. The primary outcome was hip rotation in degrees during stance phase. Secondary outcomes included temporal-spatial parameters, hip abduction, hip and knee extension, and hip and knee passive range of motion (ROM). Results : The prone group had more bilateral patients (100%) than the supine group (81%). The supine group underwent more concomitant procedures. There was no difference between the prone and supine groups in postoperative stance hip rotation; both groups had significantly improved stance hip rotation, step width, and hip rotation passive ROM, pre- to postoperatively. Prone patients had improved postoperative hip extension, pelvic tilt, velocity, and cadence. Conclusions : There was no significant different in stance hip rotation between supine and prone FDO groups. Advocates of prone positioning for FDO suggest it allows more accurate assessment of rotation. Supine positioning may be more convenient when additional procedures are required. Based on our findings, either approach can achieve the desired result.